HEPATIC ENZYME AND METABOLIC RESPONSES OF LABEO ROHITA (ROHU) TOWARDS VARYING DIETARY LIPID/PROTEIN RATIOS IN PELLETED DIETS (Journal of Medical & Health Sciences Review, 2025)
A 75-day feeding trial was conducted in a 2×2 factorial design to evaluate the effects of varying dietary lipid/protein ratios on the growth performance, hepatic enzymes, and metabolic responses of Labeo rohita (initial weight: 2.87 ± 0.01 g). Four pelleted diets containing protein levels of 250 and 300 g kg⁻¹ and lipid levels of 75 and 95 g kg⁻¹ were formulated and fed to fish (n = 10) randomly distributed into four triplicate groups (T1–T4). Fish receiving the 95/300 g kg⁻¹ lipid/protein diet (T4) attained significantly higher (p